Central Nervous System Tuberculosis: An Imaging-Focused Review of a Reemerging Disease. (12th January 2015) - Sanei Taheri, Morteza; Karimi, Mohammad Ali; Haghighatkhah, Hamidreza; Pourghorban, Ramin; Samadian, Mohammad; Delavar Kasmaei, Hosein
Abstract : Central nervous system (CNS) tuberculosis is a potentially life threatening condition which is curable if the correct diagnosis is made in the early stages. Its clinical and radiologic manifestations may mimic other infectious and noninfectious neurological conditions. Hence, familiarity with the imaging presentations of various forms of CNS tuberculosis is essential in timely diagnosis, and thereby reducing the morbidity and mortality of this disease. In this review, we describe the imaging characteristics of the different forms of CNS tuberculosis, including meningitis, tuberculoma, miliary tuberculosis, abscess, cerebritis, and encephalopathy.